An Evaluation of a Clinical Pre‐Exposure Prophylaxis Education Intervention among Men Who Have Sex with Men. (25th July 2017) - Raifman, Julia; Nunn, Amy; Oldenburg, Catherine E.; Montgomery, Madeline C.; Almonte, Alexi; Agwu, Allison L.; Arrington‐Sanders, Renata; Chan, Philip A.
Abstract : Objective: To evaluate the impact of an HIV pre‐exposure prophylaxis (PrEP) education intervention on PrEP awareness and use among men who have sex with men (MSM) attending a sexually transmitted diseases (STD) clinic. Data Sources/Study Setting: Men who have sex with men STD clinic patients. Study Design: We estimated a difference‐in‐differences linear regression model, comparing MSM whose first visit to the clinic was before ("control") or after ("treatment") intervention implementation and controlling for patient. Data Collection/Extraction: We used self‐reported data on PrEP awareness and use from STD clinic intake forms. Principal Findings: Pre‐exposure prophylaxis awareness between first and second clinic visits increased 27.2 percentage points (pp) in the treatment group, relative to 13.7 pp in the control group. Similarly, PrEP use increased 7.1 pp in the treatment group versus 2.4 pp in the control group. Based on adjusted estimates, the PrEP intervention increased PrEP awareness by 24 pp ( p  < .01) and PrEP use by 5 pp ( p  = .01), increases of 63 percent and 159 percent relative to the 6 months prior to the intervention. Conclusion: A brief, scalable STD clinic PrEP education intervention led to significantly increased PrEP awareness and use among MSM. Health care providers should consider implementing brief PrEP education interventions in sexual health care settings.